Promoting Women Entrepreneurship through Bank Credit: A Study of the NRLM Scheme - Deepshikha Patel; Anita Pandey (Involvement International Journal of Business, 2025)
The National Rural Livelihoods Mission (NRLM) is a flagship initiative by the Government of India aimed at alleviating rural poverty by promoting women entrepreneurship through Self-Help Groups (SHGs). This study examines the role of bank credit particularly from private and co-operative banks in supporting SHGs in Raigarh District, Chhattisgarh, from 2017 to 2023. This research employed a quantitative descriptive approach using secondary data on credit disbursement and outstanding amounts sourced from bank reports. Trend analysis and percentage achievement calculations were used to assess the performance of private sector and co-operative banks in achieving NRLM credit targets. Literature-based qualitative insights supported the interpretation of institutional practices and challenges. Findings indicate a significant increase in SHG credit support over time, especially from private banks, whose credit disbursement surged post-2020. Co-operative banks demonstrated strong initial involvement, although their credit achievements fluctuated in later years. Overall, both types of banks contributed meaningfully to financial inclusion for rural women, with rising loan amounts and SHG participation. While the NRLM scheme has enhanced economic and social empowerment among women, persistent challenges remain, including limited financial literacy, collateral barriers, and restricted market access. Achievement gaps between targets and outcomes in several years suggest implementation and monitoring issues. The study recommends simplifying credit processes, expanding capacity-building initiatives, and improving access to markets to further strengthen the impact of NRLM.